THE VOLCANIC DEPOSIT WEATHERED PRODUCT IN JATINANGOR AREA, WEST JAVA - Sophian, Raden Irvan; Abdurrokhim, .; Haryanto, Iyan; Hendarmawan, . (Bulletin of Scientific Contribution, 2017)
ABSTRAKPembangunan di Kawasan Jatinangor dalam beberapa waktu ini telah mengalami perkembangan yang cukup pesat. Jatinangor adalah daerah baru yang dikembangkan untuk Pendidikan dari beberapa kampus seperti Unpad, ITB, IKOPIN, dan IPDN. Hal ini menyebabkan peningkatan jumlah penduduk tiap tahunnya dan juga menyebabkan berkembangnya infrastruktur untuk mendukung kegiatan Pendidikan di daerah ini. Untuk mengetahui hambatan dan menghindari terjadinya bencana alam di masa depan, maka harus dipahami perilaku tanah permukaan sebagai pondasi bangunan berbagai sarana prasarana. Metode penelitian meliputi pemetaan geologi teknik, pengambilan sampel tanah tidak terganggu, uji tes pit, analisis sifat petrologi atau batuan. Kondisi Geologi daerah ini terdiri dari produk vulkanik muda yang tidak terpisahhkan, yang terdiri dari breksi tufan, tuf, lahar, tuf lapilli, dan abu vulkanik yang berumur kuarter (kurang dari 2 Ma). Kondisi geomorfologi daerah ini terdiri dari dataran hingga perbukitan landai di selatan Gn. Manglayang. Berdasarkan hasil penelitian, kawasan Jatinangor memiliki distribusi tanah terdiri dari lanau hingga lempung berplastisitas tinggi (MH dan CH). Kondisi ini menyiratkan produk vulkanik yang tidak terkonsolidasi dan tanah residu semi-konsolidasi sebagai produk pelapukan dari ash dan alterasi dari tuff. Kata Kunci: Jatinangor, Sifat Fisik Tanah, Tuff, Material Vulkanik Muda belum Terpisahkan ABSTRACTThe development of jatinangor area in recent time has experienced a very rapid development. Jatinangor is the new location for Education area from several campuses such as Unpad, ITB, IKOPIN, and IPDN. This results in an increase in the number of population each year and also led to a growing development of infrastructure to support educational activities in this area. To know the obstacles and avoid the occurrence of natural disasters in the future, it should be understood the behavior of surface soil as the building foundation of various infrastructure facilities. The research method includes engineering geologic mapping, undisturbed soil sampling, test pit, petrologic or rock properties analysis. The geology of this area consists of undifferentiated young volcanic product (Qyu), containing tuffaceous breccia, tuff, lava, lapilli tuff, and volcanic ash. This product is deposited on Quaternary geologic age (less than 2 Ma). The geomorphology of this area consists of plain to hilly land at the south of Mount Manglayang. Result of this study shows that around Jatinangor area the distribution of soils consists of high plasticity silt and clay (MH and CH). This condition implies to semiconsolidated-nonconsolidated volcanic product and semi-consolidated residual soil as the weathering product of ash and tuff alterations. Keywords: Jatinangor, physical properties soil, tuff, undifferentiated young volcanic product